# 45ghf(9hg+6)-9ghf+14r=

## Simple and best practice solution for 45ghf(9hg+6)-9ghf+14r= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 45ghf(9hg+6)-9ghf+14r= equation:

Simplifying
45ghf(9hg + 6) + -9ghf + 14r = 0

Reorder the terms:
45fgh(6 + 9gh) + -9ghf + 14r = 0
(6 * 45fgh + 9gh * 45fgh) + -9ghf + 14r = 0
(270fgh + 405fg2h2) + -9ghf + 14r = 0

Reorder the terms:
270fgh + -9fgh + 405fg2h2 + 14r = 0

Combine like terms: 270fgh + -9fgh = 261fgh
261fgh + 405fg2h2 + 14r = 0

Solving
261fgh + 405fg2h2 + 14r = 0

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '-14r' to each side of the equation.
261fgh + 405fg2h2 + 14r + -14r = 0 + -14r

Combine like terms: 14r + -14r = 0
261fgh + 405fg2h2 + 0 = 0 + -14r
261fgh + 405fg2h2 = 0 + -14r
Remove the zero:
261fgh + 405fg2h2 = -14r

Combine like terms: -14r + 14r = 0
261fgh + 405fg2h2 + 14r = 0

The solution to this equation could not be determined.`